2015
DOI: 10.1016/j.febslet.2015.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐dependent translocation of the heat shock transcription factor AtHSFA8 from the cytosol to the nucleus in Arabidopsis thaliana

Abstract: a b s t r a c tThe hypothesis is tested that some heat stress transcription factors (HSFs) are activated after formation of inter-or intramolecular disulfide bonds. Based on in silico analyses we identified conserved cysteinyl residues in AtHSFA8 that might function as redox sensors in plants. AtHSFA8 represents a redox-sensitive transcription factor since upon treatment of protoplasts with H 2 O 2 YFP-labeled HSFA8 was translocated to the nucleus in a time-dependent manner. Site-directed mutagenesis of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 32 publications
(56 reference statements)
1
55
0
Order By: Relevance
“…In this study, multiple of abiotic and biotic stress-responsive MaHsfs were also identified, in accordance with previous studies of Hsf gene family in other plant species12345. Based on the clues from transcript pattern, the in vivo roles of several plant Hsfs have been revealed.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this study, multiple of abiotic and biotic stress-responsive MaHsfs were also identified, in accordance with previous studies of Hsf gene family in other plant species12345. Based on the clues from transcript pattern, the in vivo roles of several plant Hsfs have been revealed.…”
Section: Discussionsupporting
confidence: 86%
“…Plant heat shock responses are mediated by heat shock elements (HSEs, nTTCnnGAAnnTTCn), which are widely present in the upstream of the heat shock proteins (HSPs)12345. The first specific transcription regulator that is responsible for HSE bindng, was characterized and confirmed as heat stress transcription factor (Hsf) in yeast ( Saccharomyces cerevisiae )6.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that HSFA4a, HSFA8 and HSFA1s can function as ROS sensors to regulate the expression of HS‐induced oxidation‐related genes in plants (Miller and Mittler ; Dickinson et al ). Mutation of conserved cysteine residues (Cys 24 and Cys 269 on HSFA8, but Cys 153 and Cys 357 on HSFA1d) inhibits the H 2 O 2 ‐induced nuclear translocation of HSFA8 (Giesguth et al ), as well as impairs HSFA1d's ability to activate the expression of APX2 under high‐light conditions (Jung et al ). However, HS treatment did not induce the nuclear translocation of HSFA8, suggesting that the redox‐sensing function of HSFA8 may not directly regulate HS‐related gene expression (Giesguth et al ).…”
Section: Heat Shock Signaling Mechanismsmentioning
confidence: 99%
“…Thiol-disulfide transitions, on the other hand, are frequently associated with redox regulation in plants. For instance, intra-or intermolecular Cys-Cys formation is believed to determine the nuclear localization of the redox TF HSFA8 in response to H 2 O 2 (Giesguth et al, 2015). Despite the fact that redox-sensitive nonclustered cysteines have been identified and examined in plant transcription factors before (Schmidt and Schippers, 2015), they have never been found to belong to the set of Met-Cys initiating ("MC") proteins.…”
Section: N-terminal Cys Modificationsmentioning
confidence: 99%